Difusão de documentos fotográficos: análise de experiências de três instituições arquivísticas brasileiras no Facebook - Suellen Alves de Melo (2019)
This work aims at analyzing how photographic documents are disseminated on social media, mainly on Facebook Pages from Brazil Public Archives. Three Brazilian public archival institutions were selected to be analyzed: Arquivo Nacional (National Archive), Arquivo Público do Estado de São Paulo (São Paulo state Public Archive) e Arquivo Público da Cidade de Belo Horizonte (Belo Horizonte city Public Archive). The research methodology employed quantitative and qualitative techniques. The posts made in 2017 and 2018 on the Facebook pages of the institutions were counted to verify how the photographs are disseminated, as well as if they are shared in greater numbers than other documentary genres guarded by the analyzed institutions. In addition, the technicians responsible for diffusion in the selected institutions were interviewed, seeking to verify if the Archives Institutions have diffusion policies and if they are respected in practice. The results showed that, among documentary genres, photography is the most widespread document by the analyzed institutions. The main funds used for the dissemination of photographs are documentary sets produced by private newspapers and State Press Offices, as they contain photographic documents of various natures. Posts that use photographs are produced in order to reach the public from ephemeris, personalities, places, among other themes. Although not all institutions have a dissemination policy in place for their work on Facebook, the archives analyzed have consolidated procedures for their practices in this social network. Finally, as diffusion is an activity that involves power, this paper proposes that institutions have diffusion policies integrated in their archival policies, in order to make clear all aspects of their lines of action related to diffusion, as well as this document is known both internally and to the general public.